Using the Integral Digital Twin for Product Carbon Footprint calculation - Sven Winter; Niklas Quernheim; Lars Arnemann; Phillip Bausch; Nicholas Frick; Joachim Metternich; Benjamin Schleich (Cleaner Environmental Systems)
Sustainable product development and manufacturing rely heavily on digital technology, as evaluating sustainability metrics requires the systematic gathering and organization of information throughout the product life cycle (PLC). A suitable technology to utilize the potential for sustainability improvement of products is the Digital Twin (DT). This paper introduces the concept of the Integral Digital Twin (IDT) in the context of ecological sustainability as a central data space and application hub for data-driven sustainability. It integrates horizontal communication with clients and suppliers and vertical communication within a company's information systems. The IDT incorporates data generated at various product life phases, providing interfaces for integrating external and the creation of internal eco-databases, along with sustainability metrics calculation tools. Central to this framework is the data model, facilitating the management and distribution of sustainability-relevant data within the IDT. The proposed concept adds value by integrating sustainability assessment in the form of the Product Carbon Footprint (PCF) into DT technology, establishing a dedicated data space within the IDT for this purpose. The novelty of the approach lies in the linking of different DT and software systems across several PLC phases, enabling holistic sustainability management for different perspectives such as product or factory level perspectives. The data model of the IDT provides a basis for an interoperable and seamless data exchange of sustainability relevant data such as the PCF across all stakeholders in the PLC.